2016
DOI: 10.1007/s13139-016-0430-0
|View full text |Cite
|
Sign up to set email alerts
|

Visual Pattern and Serial Quantitation of 18F-Sodium Fluoride PET/CT in Asymptomatic Patients After Hip and Knee Arthroplasty

Abstract: This is the first F-sodium fluoride PET/CT study investigating the stability of implants and sets a reference for evaluation of patients with complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
(44 reference statements)
1
9
1
Order By: Relevance
“…The uptake patterns found in our study show some differences from those found in previous studies [4]. Our study describes a gradual increase in bone-forming activity for the first 7 days after surgery.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…The uptake patterns found in our study show some differences from those found in previous studies [4]. Our study describes a gradual increase in bone-forming activity for the first 7 days after surgery.…”
Section: Discussioncontrasting
confidence: 96%
“…In 2016, Son et al [4] firstly reported the visual and quantitative analysis of [ 18 F] NaF uptake after joint replacement. In their study, however, the interval between the surgery and the scan was from 3 to 25 months; [ 18 F] NaF PET analysis was not performed within 3 months and after more than 25 months after the surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The criteria we used in our current study to differentiate non-specific uptake of 18 F-Fluoride from patterns specific for loosening are in close correlation with uptake patterns described by Son et al, who previously examined postoperative 18 F-Fluoride uptake in asymptomatic patients up to 25 months after hip or knee arthroplasty [21]. Our criteria for non-specific uptake correspond to areas of the bone interface which showed intense uptake in more than 75% of asymptomatic patients in the study by Son et al (Normal or no uptake see Figure 1 (A,D)) Specifically, these are the cranial and caudomedial parts of the acetabular component and the distal tip of the femoral component of hip prostheses.…”
Section: Methodssupporting
confidence: 54%
“…Besides hip arthroplasty, NaF-PET has been used to image knee, ankle, and shoulder arthroplasties. [121][122][123][124][125] A study that included 24 hip and 13 knee prostheses found that NaF-PET/CT had a sensitivity of 95% and a specificity of 87% in diagnosing periprosthetic loosening (Fig. 4).…”
Section: Orthopedic Complicationsmentioning
confidence: 99%